2019
DOI: 10.14740/jh487
|View full text |Cite
|
Sign up to set email alerts
|

Legionella-Induced Autoimmune Hemolytic Anemia: A Delayed and Unexpected Complication

Abstract: Legionella pneumophilia is a multi-systemic disease primarily affecting the pulmonary, gastrointestinal, and to a lesser extent, renal systems. We present a case of Legionella pneumonia, which after resolution of respiratory compromise, was complicated by the development of autoimmune hemolytic anemia (AIHA) as determined by a positive Coombs test, and negative workup of other causes. Steroid immunosuppression was initiated, and red cell counts subsequently improved. While AIHA has only been anecdotally descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…LP is frequently associated with hyponatremia [23], which may in turn be associated with the syndrome of inappropriate antidiuretic hormone secretion [27]. There is some anecdotal evidence associating hemolytic anemia to legionellosis, but the underlying mechanism is unknown [28,29]. However, in our study, the bilirubin levels in both LP and psittacosis patients were found to be in the normal range, suggesting no evidence of hemolytic anemia.…”
Section: Discussioncontrasting
confidence: 43%
“…LP is frequently associated with hyponatremia [23], which may in turn be associated with the syndrome of inappropriate antidiuretic hormone secretion [27]. There is some anecdotal evidence associating hemolytic anemia to legionellosis, but the underlying mechanism is unknown [28,29]. However, in our study, the bilirubin levels in both LP and psittacosis patients were found to be in the normal range, suggesting no evidence of hemolytic anemia.…”
Section: Discussioncontrasting
confidence: 43%
“…While Mycoplasma species are frequently associated with CAS, there is a lower association with Legionella. There are only five case reports published at the time of this submission of an AIHA associated with Legionella, and only one published associated with cold agglutinin [6][7][8]. This raises the possibility of underdiagnosis of AIHA secondary to Legionella.…”
Section: Discussionmentioning
confidence: 94%